Substance use among sexual and gender minorities: Association with police discrimination and police mistrust. Issue 2 (29th June 2020) - Lipperman‐Kreda, Sharon; Wilson, Ida; Hunt, Geoffrey P.; Annechino, Rachelle; Antin, Tamar M. J.
Abstract: We investigated associations between experiences with police discrimination, police mistrust, and substance use in a convenience sample of 237 sexual and gender minority (SGM) adults in California. In a cross‐sectional survey, collected between January 2016 and July 2017, participants reported substance use, lifetime experiences with SGM‐related police discrimination, police mistrust, demographics, and SGM visibility. In adjusted logistic regression models, we found a positive association between lifetime police discrimination and past 2‐week heavy episodic drinking. Police mistrust also was positively associated with past month marijuana use. Several significant interactions between lifetime police discrimination or police mistrust with other socially stigmatized identities including being African American, insecure housing, and being a gender minority on a few substance use outcomes suggest that effects of police discrimination and mistrust on substance use are stronger among participants with multiple stigmatized identities. Results suggest the importance of policies and interventions that focus on eliminating police discrimination and increasing police legitimacy to reduce risk of substance use among SGM individuals.